Simulating cognitive coping strategies for intelligent support agents - Ab. Aziz, Azizi; Klein, Michel C. A.; Treur, Jan (2010)
People react differently to stress.According to the Cognitive Motivational Relational Theory by Lazarus and Folkman, the appraisal of stress and the emotions related to it determine whether people cope with stress by focusing on altering the situation (problem focused) or on changing the emotional consequences of the events (emotion focused). These different coping strategies have different effects on the long term.The coping process can be described in a formal dynamic model. Simulations using this model show that problem focused coping leads to better coping skills and higher decrease of long-term stress than emotion focused coping.These results also follow from a mathematical analysis of the model.The presented model can form the basis of an intelligent support system that uses a simulation of cognitive processes in humans in stressful conditions.